2017
DOI: 10.1007/s11239-017-1525-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between aspirin use and deep venous thrombosis in mechanically ventilated ICU patients

Abstract: Deep venous thrombosis (DVT) is common in intensive care unit (ICU) patients. It is often silent and may be complicated by pulmonary embolism and death. Thromboprophylaxis with heparin does not always prevent venous thromboembolism (VTE). Aspirin (ASA) reduces the risk of VTE in surgical and high-risk medical patients but it is unknown if ASA may prevent DVT in mechanically ventilated ICU patients. We performed a retrospective chart review of critically ill patients who received mechanical ventilation for >72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Aspirin has been shown to decrease the risk of VTE in surgical and high-risk medical patients but its effects in mechanically ventilated ICU patients are unknown. A study designed to investigate the effect of aspirin on thromboembolic events in mechanically ventilated patients showed a significant reduction in the odds of finding DVT with aspirin (OR 0.39, 95% CI 0.16–0.94; p = 0.036) [ 42 ]. So, aspirin may be helpful in preventing DVT in such patients.…”
Section: Reviewmentioning
confidence: 99%
“…Aspirin has been shown to decrease the risk of VTE in surgical and high-risk medical patients but its effects in mechanically ventilated ICU patients are unknown. A study designed to investigate the effect of aspirin on thromboembolic events in mechanically ventilated patients showed a significant reduction in the odds of finding DVT with aspirin (OR 0.39, 95% CI 0.16–0.94; p = 0.036) [ 42 ]. So, aspirin may be helpful in preventing DVT in such patients.…”
Section: Reviewmentioning
confidence: 99%
“…There was one study (198 patients) involving a specialized cardiac ICU (36), three studies (3,317 patients) involving neurologic ICUs (37)(38)(39), and four studies (1,101 patients) involving trauma ICUs (40)(41)(42)(43). Most studies evaluated any symptomatic VTE (DVT or PE) as the primary outcome, though some studies evaluated only DVT (2,(44)(45)(46)(47), only PE (6,36,37,40,(48)(49)(50), or only CVC-associated DVT (39,51). Of the 20 studies evaluating lower e373 extremity DVTs, nine studies included both proximal and distal DVTs (38,43,47,(52)(53)(54)(55)(56).…”
Section: Search Resultsmentioning
confidence: 99%
“…At present, no clinical trials exist that relate the use of antiplatelet agents in critically ill patients in prophylactic anticoagulation. In a retrospective study of 193 mechanically ventilated patients, multivariate regression analysis showed that the use of aspirin during hospitalization could reduce the risk of DVT (OR = 0.39, 95% CI = 0.16-0.94) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%